The Efforts of Government to Overcome Farmer Losses Due to Crop Failure in The Form of Protection for Farmers in Kwadungan District, Ngawi Regency Based on Laws - Muttaqin, Ma’arif Rozaq; Ridho, Irvan Nur (Journal of Research in Social Science and Humanities, 2022)
The purpose of the study was to determine the government's efforts to overcome farmers' losses due to crop failure in Kwadungan District, Ngawi Regency based on legislation as a form of protection for farmers. The type of research used by the researcher is a qualitative method with a descriptive approach. The informant determination technique used in this research is purposive sampling technique. The data collection method used in this research is by observation and interviews. The method of data analysis is descriptive qualitative analysis. The conclusion that can be obtained is that the stages of AUTP implementation that have been carried out are of course in accordance with the program implementation guidelines that have been regulated in the AUTP program implementation guidelines to minimize losses due to crop failure in Ngawi Regency, namely: a) The preparation stage by conducting outreach to farmers. b) The implementation stage is to provide guidance and counseling to farmers. c) Monitoring, evaluation and reporting where this is the last stage carried out when the rice has been harvested.  Abstrak: Tujuan penelitian yaitu untuk mengetahui upaya pemerintah dalam mengatasi kerugian petani akibat gagal panen di Kecamatan Kwadungan Kabupaten Ngawi berdasarkan Perundang-Undangan sebagai bentuk perindungan petani. Jenis penelitian yang digunakan oleh peneliti adalah metode kualitatif dengan pendekatan deskriptif. Teknik penentuan informan yang dilakukan dalam penelitian ini adalah teknik purposive sampling. Metode pengambilan data yang digunakan dalam penelitian ini yaitu dengan observasi dan wawancara. Metode analisis data ialah analisis deskriptif kualitatif. Kesimpulan yang dapat diperoleh yaitu Tahapan penerapan AUTP yang telah dilakukan tentunya sesuai dengan pedoman pelaksanaan program yang telah diatur dalam pedoman pelaksanaan program AUTP untuk meminimalisir kerugian akibat gagal panen di Kabupaten Ngawi yaitu: a) Tahap persiapan dengan melakukan sosialisasi kepada para petani. b) Tahap pelaksanaan dengan melalukan bimbingan dan penyuluhan terhadap petani. c) Monitoring, evaluasi dan pelaporan dimana ini merupakan tahap terakhir yang dilakukan ketika padi sudah panen.